Identifying an educational-economic code of quality in definitions of extended education: an example from school leaders in Sweden - Manni, Annika; Norqvist, Maria; Yttergren, Susanne (Frontiers in Education, 2025)
Knowledge about how quality in extended education is defined, formulated, and communicated regarding quality-related problems in educational practices, and school leaders’ roles in these processes is limited. This article presents findings from research focusing on educational quality in extended education in Sweden (commonly known as School-age educare) is defined by school leaders in one Swedish municipality. The data examined written documents associated with governance and organizations of School-age educare created by school leaders at different levels of one Swedish municipality. The analysis of data was based on the concepts of Bernstein’s pedagogical codes (2003), and from Scherp and Scherp's School organization model (2007). The results revealed that the educational-pedagogical code dominated, and the leisure-pedagogical and social-pedagogical codes only appeared sporadically in the analyzed documents. A new ‘educational-economic’ pedagogical code emerged during analysis. It included formulations indicating that quality can be addressed by economic actions. The analyzed documents revealed power structures between different levels of school leaders, and also a lack of shared understanding and definition of quality in extended education. School leaders should discuss, and agree on, what quality in extended education includes and not only rely on quantitative and measurable aspects of this educational practice.